Тhe Class Teacher in the System of Pedagogical Work of Schools - Jovanović, Branko; Đurić, Igor R. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
By the method of theoretical analysis and modeling, this paper explains the meaning, role, status and duties of the class teacher in the system of educational work of contemporary schools. The class teacher represents the fundamental, irreplaceable and the most important factor in the system of educational work of contemporary schools. The class teacher is simultaneously a teacher, educator, planner, organizer, implementer and evaluator of teaching and educational work with the students, but also an associate and coordinator in working with other teachers, support staff, parents and other subjects, professional authorities and institutions involved in the realization of educational work with the collective of class students. Educational work of class teachers is often characterized by authoritarian and elemental style of work, formalistic approach in implementation of pedagogical work, pedagogical inconsistency, lack of pedagogical enthusiasm, empathy, creativity and responsibility. There are numerous reasons that affect the insufficient quality work of class teachers. It is objectively difficult to realize the goals of educational work in the conditions of crisis, students` value disorientation and disturbed system of values in which our society is nowadays. Class teachers are not sufficiently motivated and pedagogically trained to implement numerous and complex tasks. Without proper support, control and assistance of the school management, they usually resort to the application of traditional methods and procedures of educational work based on the concept of authoritarian upbringing and insufficiently studious and responsible realization of their teaching duties. To successfully perform very complex, responsible and demanding pedagogical duties of class teachers , it is necessary to undertake a series of systematic measures in: intensifying the educational work of schools; training of teachers – future class teachers during their preparation for the teaching profession; the design and implementation of programs of permanent education and self-improvement of class teachers; and improving the position of the status the teaching profession.